IMPLEMENTASI TEKNOLOGI 3D AUGMENTED REALITY UNTUK PEMETAAN GEDUNG SMK YADIKA BANGIL - mualim, wildan; Roji, Mukhamad Fatkhur (SPIRIT, 2022)
Abstract: At this time the Covid-19 pandemic was hit Indonesia. This new normal condition is very influential on activities in the school world. One of them was during the Introduction to School Environment Introduction as we call (MPLS) which should have been done face-to-face to get to know the school more deeply, replaced by online, so that new students could not get to know more about the school building. So it takes a picture of the building in the form of 3-dimensional visual multimedia (3D) using Augmented Reality (AR) technology. Based of these problems, an Android - based application was made using AR (Augmented Reality) technology. With this application, users, especially new students, can find out more details about the locations or rooms on the Yadika Vocational High school via their smartphones.